PHONOLOGICAL CHANGE PROCESSES OF ENGLISH AND INDONESIAN - Irma Diani; Azwandi Azwandi (JOALL (Journal of Applied Linguistics and Literature), 2021)
Phonological change is a language phenomenon that occurs because language users change the distribution of phonemes in a language. The aims of this study are to explain the phonological processes that occur in English and Indonesian and to explain the differences in phonological forms between English and Indonesian. The method used in this study is a contrasting-descriptive method by comparing two languages, namely English and Indonesian. The data were taken from the speech of students taking Indonesian and English courses at the University of Bengkulu, totaling 40 students in the first semester. The results show that five types of phonological change processes occurred in English and Indonesian, namely assimilation, metathesis, epenthesis, epithesis, and deletion. The phonological change in English often occurred when two vowel phonemes meet, such as /ea/ shift to /e/, or /i/, phoneme /y/ shift to /i/. Phoneme /e/ was pronounced when two vowel phonemes meet, such as /s/ and /n/ becomes /sen/. Phoneme /g/ is pronounced multiply when it meets the sound/ng/. Phoneme /u/ is pronounced when it meets phoneme /o/ + a consonant. Phoneme /h/ is unpronounced when it meets a vowel phoneme or more vowel phonemes in the words. Meanwhile, phonological changes in Indonesian often occurred from consonant phonemes to other consonant phonemes that have almost the same sound such as phoneme /z/ shift to /s/ and /j/. Phoneme /k/ was pronounced after phoneme /u/ and phoneme /h/ is pronounced after phoneme /a/at the end of words. Phoneme /y/ was pronounced between phonemes /i/ and /a/. Phoneme /h/ was unpronounced when it meets phonemes /a/, /i/, and /u/ in words. In conclusion, the process of phonological change that occurs in English and Indonesian is due to the influence of adjacent phoneme sounds that resemble nearby sounds.